The correct answer is 537
a is given to us so just plug a into the first equation:
b-3 - 3b =9
Add 3 to both sides:
b-3b=12
Combine like terms:
-2b=12
Divide by -2 to get b by itself:
b=-6
The only answer with b as -6 is the first one, (-9,-6)
Answer:
y = -6
Step-by-step explanation:
y=acos(bx+c)+d
d = -6 .. vertical shift
midline: y = -6
Answer:
noe lsoocslo oqiuepcn
Step-by-step explanation:
mcm
Answer:
First Problem:
1/2 * -2 2/5 = 1/2 * -12/5 = -12/10
Simplify -12/10 into -6/5
Step-by-step explanation: